Inhibition of autolysosomes by repurposing drugs as a promising therapeutic strategy for the treatment of cancers - Abdul Alim Al-Bari (All Life, 2022)
Autophagy process coordinates lysosomal destruction of cytoplasmic materials including damaged organelles and proteins. The double-membranous ‘autophagosome’ selectively sequesters the cytosolic components, followed by ‘autolysosome’ formation for degradation. By recycling energy, autophagy preserves intracellular homeostasis. Autophagy also acts a crucial function in various cellular events including cell survival and death in response to stressed conditions. Thus, any dysfunction in autophagy causes a wide variety of pathologies including cancers. Multiple lines of evidence have decorated the importance of autophagy for the regulation of cancer development. Aberrant autophagy can govern healthy normal cells to endure the transformation of malignant cells. By comparison, cancer cells are apt to control autophagy to bloom it and to repel therapeutic challenges. Hence, the modulation of autolysosomes can assassinate malignant cells or sharpen them for therapy. Most current research is trying to manipulate autophagy appropriately for cancer therapies and a wide variety of medical objectives are turning forward to inhibit the acidification of lysosomes and autolysosomes with repurposing drugs. This review explores the lysosomotropic agents be utilized to treat cancers through their inhibiting roles in the acidification system and discuss the preclinical and clinical clues for hints the next generation of pharmacological agents for the treatment of cancers.